TAFSIR AL-QUR'AN DI ERA POST-TRUTH: ANALISIS WACANA TAFSIR LISAN ACH DHOFIR ZUHRY - Fakhri Afif; Subi Nur Isnaini (UIN Raden Mas Said Surakarta, 2023)
This study aims to explain Ach Dhofir Zuhry's oral interpretation of the Qur'an that discusses post-truth discourse. The emergence of post-truth in recent years seems to have eliminated the dividing line between truth and falsehood. Consequently, digitalization presents significant negative impacts in the social, economic, political, and, of course, religious dimensions. In addition, post-truth also opens opportunities for religious people to improve their religious understanding, but on the other hand, the digital world contributes to the increasing issue of religious intolerance and exclusivism. Along with this phenomenon, Ach Dhofir Zuhri came up with an interpretation of the Qur'an through oral speech delivered through social media platforms. Based on qualitative data, this study analyzes literature and digital data, as well as interviews with Dhofir Zuhry. By elaborating on the idea of oral interpretation and modern interpretive discourse, this study shows that Zuhry's oral interpretation in the digital world offers a new perspective on the discussion of Islam and post-truth. In this case, the concept of tabayyun becomes an ethical-contextual solution to face the post-truth era by encouraging the maximum utilization of human reason in social media.